1979
DOI: 10.1016/s0072-968x(79)80048-0
|View full text |Cite
|
Sign up to set email alerts
|

Injuries of the Proximal Interphalangeal Joint of the Fingers

Abstract: A consecutive group of ninety-three patients with ninety-six affected joints, have been reviewed retrospectively to provide information regarding the incidence and longer term effects of injuries to the proximal interphalangeal joint of the fingers. The patients have been grouped according to the severity of the injury, judged clinically and radiologically. From this review it would appear that these injuries are somewhat less common than is suggested in the literature. The severity of the trauma would seem to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
4

Year Published

1989
1989
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 8 publications
0
6
0
4
Order By: Relevance
“…However, there is no clear consensus on the treatment of injuries of the collateral ligament of the PIP joint (3,9). An injured ligament with instability greater than 20°or with no end point on manual stress is considered to be a complete rupture (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is no clear consensus on the treatment of injuries of the collateral ligament of the PIP joint (3,9). An injured ligament with instability greater than 20°or with no end point on manual stress is considered to be a complete rupture (9,15).…”
Section: Discussionmentioning
confidence: 99%
“…Der resultierende Verlust von Kollagen kann somit zur Entwicklung einer Beugekontraktur führen [8][9][10][11]. In der Literatur wird vor allem die Beugekontraktur als komplizierende Langzeitfolge beschrieben und scheint die größte therapeutische Herausforderung zu sein [5,8,12,13]. Wenn sich andererseits die rupturierten Stumpfenden der palmaren Platte nicht adaptieren, geht man davon aus, dass sie in Überlänge vernarben und so zu einer palmaren Instabilität resp.…”
Section: Introductionunclassified
“…Benke and Stapleforth in a retrospective review of 96 PIP joint injuries found a poor outcome in 30 % (almost half of which had open injuries), as characterized by pain, poor function, joint instability, or stiffness in the form of fl exion deformities [ 29 ].…”
Section: The Proximal Interphalangeal Joint: (Pipj) Introductionmentioning
confidence: 99%